Genomic relationships among diploid and polyploid species of the genus Ludwigia L. section Jussiaea using a combination of molecular cytogenetic, morphological, and crossing investigations - Barloy, Dominique; Portillo-Lemus, Luis; Krueger-Hadfield, Stacy; Huteau, Virginie; Coriton, Olivier (Peer Community Journal)

(untitled)
The genus Ludwigia L. section Jussiaea is composed of a polyploid species complex with 2x, 4x, 6x and 10x ploidy levels, suggesting possible hybrid origins. The aim of the present study is to understand the genomic relationships among diploid and polyploid species in the section Jussiaea. Morphological and cytogenetic observations, controlled crosses, genomic in situ hybridization (GISH), and flow cytometry were used to characterize species, ploidy levels, ploidy patterns, and genomic composition across taxa. Genome sizes obtained were in agreement with the diploid, tetraploid, hexaploid, and decaploid ploidy levels. Results of GISH showed that progenitors of Ludwigia stolonifera (4x) were Ludwigia peploides subsp. montevidensis (2x) and Ludwigia helminthorrhiza (2x), which also participated for one part (2x) to the Ludwigia ascendens genome (4x). Ludwigia grandiflora subsp. hexapetala (10x) resulted from the hybridization between L. stolonifera (4x) and Ludwigia grandiflora subsp. grandiflora (6x). One progenitor of L. grandiflora subsp. grandiflora was identified as L. peploides (2x). Our results suggest the existence of several processes of hybridization, leading to polyploidy, and possibly allopolyploidy, in the section Jussiaea due to the diversity of ploidy levels. The success of GISH opens up the potential for future studies to identify other missing progenitors in Ludwigia L. as well as other taxa.